THE ESSENCE AND POLITICAL CATEGORICAL ANALYSIS OF THE CONCEPTS OF “YOUTH,” “EXTREMISM,” AND “INTOLERANCE” - Mansur Uralov (The Conference Hub, 2025)
This article examines the political categorical analysis of the concepts of youth, extremism, and intolerance. It highlights the role of youth in society, the emergence of extremism as a global threat, and intolerance as its main cause. Based on Karl Popper’s theory of the “paradox of tolerance,” the issue of intolerance is discussed, emphasizing the necessity of effective political strategies to combat extremism.
Keywords: Youth, extremism, intolerance, political categories, paradox of tolerance.